2023
DOI: 10.1002/pc.27925
|View full text |Cite
|
Sign up to set email alerts
|

Low‐velocity impact response and post‐impact assessment of self‐healing composites with different stacking configurations of core–shell nanofibers

Haopeng Cai,
Yu Gan,
Boxue Chen
et al.

Abstract: This work investigates the low‐velocity impact (LVI) and self‐healing behavior of carbon fiber composite laminates interlaced with electrospun polyacrylonitrile core–shell nanofibers (PAN@CFRP). The main goal is to investigate the influence of different stacking configurations of core–shell nanofibers on the impact resistance and self‐healing properties of composite laminates. To achieve the purpose, three different stacking configurations were designed and tested alongside virgin specimens. The damage mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Cai et al investigated the post‐impact self‐healing efficiency of polyacrylonitrile core–shell nanofibers interleaved carbon composites. Different stacking configurations were employed for that purpose to report the highest recovery rate of 80% of the pre‐impact flexural strength 14 . In a similar vein, Wan et al confirmed the self‐healing capacity of CNT reinforced core–shell electrospun nanofibre interleaved composites 15 .…”
Section: Introductionmentioning
confidence: 93%
“…Cai et al investigated the post‐impact self‐healing efficiency of polyacrylonitrile core–shell nanofibers interleaved carbon composites. Different stacking configurations were employed for that purpose to report the highest recovery rate of 80% of the pre‐impact flexural strength 14 . In a similar vein, Wan et al confirmed the self‐healing capacity of CNT reinforced core–shell electrospun nanofibre interleaved composites 15 .…”
Section: Introductionmentioning
confidence: 93%